Is Arsenic Exposure a Risk Factor for Metabolic Syndrome? A Review of the Potential Mechanisms - Pánico, Pablo; Velasco, Myrian; Salazar, Ana María; Picones, Arturo; Ortiz-Huidobro, Rosa Isela; Guerrero-Palomo, Gabriela; Salgado-Bernabé, Manuel Eduardo; Ostrosky-Wegman, Patricia; Hiriart, Marcia (Frontiers in Endocrinology, 2022)
Exposure to arsenic in drinking water is a worldwide health problem. This pollutant is associated with an increased risk of developing chronic diseases, including metabolic disorders. Metabolic syndrome (MS) is a complex pathology that results from environmental and genetic factors. This condition increases the risk of developing type 2 diabetes, cardiovascular diseases, and cancer. The MS includes at least three of the following signs, central obesity, impaired fasting glucose, insulin resistance, dyslipidemias, and hypertension. Here, we summarize the existing evidence of the multiple mechanisms triggered by arsenic to develop the cardinal signs of MS, showing that this pollutant could contribute to the multifactorial origin of this pathology.